Gastroprotective effect of aqueous extract and mucilage from Bryophyllum pinnatum (Lam.) Kurz - Sharma, Abhishek L. (Anc Sci Life, 2014)
CONTEXT: Bryophyllum pinnatum is used as traditional medicine in India, Africa, Tropical America and China for treatment of various diseases. B. pinnatum contains different groups of phytoconstituents viz., flavonoid, terpenoids, alkaloid, phenolic compounds. AIM: The present study was carried out to evaluate the gastroprotective activity of B. pinnatum whole plant aqueous extract, and mucilage (MUC) isolated from the whole plant against ethanol induced gastric ulcer. MATERIALS AND METHODS: Pretreatment of rats with aqueous extract at dose level of 500 and 750 mg/kg b.w., MUC at 500 mg/kg dose level and standard drug Rabeprazole at dose level of 20 mg/kg b.w. where given for 7 days. RESULTS: The aqueous whole plant extract of B. pinnatum at dose of 750 mg/kg p.o. and MUC at dose of 500 mg/kg p.o. markedly decrease the incidence of ulcers in ethanol induced ulcer rats. In ethanol induced ulcer rats, there was a decrease in the gastric volume, free and total acidity and ulcerative index as compared to the control group. Total carbohydrate content was found to be an increase as compare to control the group. The aqueous whole plant extract of B. pinnatum at dose of 750 mg/kg showed a significant reduction in the above parameters which was comparable to the standard drug rabeprazole (20 mg/kg). B. pinnatum extract and MUC showed protection index 72.69 and 69.65% respectively, whereas standard drug rabeprazole showed protection index 75.49%. CONCLUSIONS: Whole plant extracts of B. pinnatum and MUC has potent gastroprotective effect which can be further clinically studied for new drug development.